Modes of drought climatization: A frame analysis of drought problematization in Germany across policy fields - Wibke Müller; Sylvia Kruse (Environmental Policy and Governance, 2021)
Since 2003, droughts have been problematized within a climate change frame in Germany. Scholars describe this framing process as climatization. In our research, we conduct a qualitative content analysis of sector journal articles to investigate the climatization of drought within the three most affected policy fields in Germany: agriculture, water management, and forestry. The research objectives are to investigate how climatization processes evolve and take place within a specific policy field, and what different modes of climatization can be identified. The results are based on a framing analysis of 267 articles from journals published by political associations of farmers, water managers, and foresters at both the national and a state level, covering drought problematization relating to two major drought events in 2003 and 2011–2012. The article shows that four modes of climatization can be distinguished: scientification, securitization, technocratization, and transformation. With this empirically based heuristic, we contribute to advancing the concept of climatization by operationalizing it into a more profound, empirically grounded analytical concept that can be applied to critically investigate policymaking processes related to reducing disaster risks and achieving climate adaptation.
Keywords: 330; climate change; climatization; drought; frame analysis; Germany